MANAGEMENT OF AMAVATA (RHEUMATOID ARTHRITIS) WITH YOGA THERAPY - Debnath, Saroj Kumar; Chandra Dash, Suresh; Vyas, Gourang Jagdishchandra (International Journal of Ayurveda and Pharma Research, 2015)
Amavata may be simulated with Rheumatoid arthritis on the basis of clinical manifestation and pathogenesis. In this clinical study, 43 Amavata (Rheumatoid arthritis) patients were registered from the O.P.D. of the Maharshi Patanjali Institute for Yoga Naturopathy Education and Research, Gujarat Ayurved University, Jamnagar. Among 43, 3 patients discontinued before completion of the treatment. Yoga therapy i.e. Prarthana (Prayer), Sutraneti, Jalaneti, Vaman (kunjal), Kapalbhati, Stretching and Rotations, Asana, Mudra, Pranayam, Relaxation with Dharana, Omkara & Shanti mantra were designed in the treatment of Amavata (Rheumatoid arthritis) patients for three weeks (21 days). The practice was performed on an empty stomach. In the clinical study, 60 % of the participants showed major improvement, 35% minor improvement and 5% no improvement. Complete remission was nil. No complication was found in the clinical study. Maximum participants were women whose age ranged between 30 to 50 years.